Measurement of Androgen and Estrogen Concentrations in Cord Blood: Accuracy, Biological Interpretation, and Applications to Understanding Human Behavioral Development - Hollier, Lauren P.; Keelan, Jeffrey A.; Hickey, Martha; Maybery, Murray T.; Whitehouse, Andrew J. O. (Frontiers in Endocrinology, 2014)
Accurately measuring hormone exposure during prenatal life presents a methodological challenge and there is currently no “gold standard” approach. Ideally, circulating fetal hormone levels would be measured at repeated time points during pregnancy. However, it is not currently possible to obtain fetal blood samples without significant risk to the fetus, and therefore surrogate markers of fetal hormone levels must be utilized. Umbilical cord blood can be readily obtained at birth and largely reflects fetal circulation in late gestation. This review examines the accuracy and biological interpretation of the measurement of androgens and estrogens in cord blood. The use of cord blood hormones to understand and investigate human development is then discussed.